Measuring inter-organizational cost management and open book accounting - Bakil DhaifAllah,; Sofiah Md. Auzair,; Ruhanita Maelah,; Md Daud Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper reports the findings of a study aimed at developing valid measurement for interorganizational cost management (IOCM) and open book accounting (OBA) constructs. The conceptualization of these measures were based on the prior literature in the context of supplier firms of Malaysian manufacturing sector. Using Structural Equation Modelling (SEM), measurement models of the constructs were tested and the scales were validated. The results indicated a satisfying model with acceptable reliability and validity. The findings of this study provide instruments that could be utilized as tools to assess the adoption of IOCM and OBA practices in buyer-supplier relationships. This paper extends the understanding on the concepts of IOCM and OBA practices through the introduction of a comprehensive scale covering wide dimensions of IOCM and OBA.